Practices and Perspectives in Using Vlogs as Speaking Performance Assessment: A Proposed Assessment Tool - Manuel, Mac Jerome M. (Future Science / FSH-PH Publications, 2024)
In the twenty-first century, the use of technology in the teaching process has become increasingly crucial. A rising trend in language assessment comes in the form of vlogs. Its proliferation in language assessment can serve many advantages and benefits. However, a misguided assessment strategy can undermine the teaching-learning process. Also, learners often feel that vlogging assessments need to be revised because the focus is on the vlogging skills and media quality. Hence, the study aimed to identify the practices and perspectives of language teachers, academic heads, and language learners in using vlogs as a speaking performance assessment. A qualitative design was employed to collect a rich and detailed understanding of the focus of the study. The informants were selected through purposive sampling. Data were collected through essay questionnaires, focus-group discussions, and semi-structured interviews. The findings revealed that using vlogs in language assessment offers a versatile and practical approach for formative and summative purposes. Administering vlogging tasks requires weighing the advantages and challenges associated with each approach. Vlog types, such as personal vlogs, opinion vlogs, and interview vlogs, are ideal for enhancing learners' speaking skills. Furthermore, the pedagogical considerations of language teachers in utilizing vlogs include alignment, sufficient time and support, access to necessary technological resources, learner flexibility, support to struggling learners, clear and comprehensible instructions, and equity for all learners. There is a consensus on the significance of content, creativity, presentation, proficiency, fluency, and technical quality as criteria in vlog assessment.